Hoof conformation and performance in the racing Thoroughbred in Macau. Issue 3 (19th December 2012) - Cust, ARE; Anderson, GA; Whitton, RC; Davies, HMS
<x xml:space="preserve">Abstract</x> Objectives To investigate associations between race performance and hoof–ground angle (HG), pastern–hoof angle (PH) and mediolateral hoof angle (ML) of the left forelimb. Methods A total of 1570 starts were recorded from 636 horses, and meetings were equally divided between sand and turf tracks. HG, PH and ML were measured on each starter in a race, over a 3‐month period, using a Finnegan hoof gauge (Tallahesse Asia Holdings Ltd, Hong Kong) and digital photographic images. Race performance was recorded as win or place (1st–3rd). Results There was no association between the probability of winning or placing and gauge HG, photographic HG or photographic ML. There was a significant negative association between PH and the probability of winning on the turf track. On the turf surface, the odds ratio of winning for each 1° decrease in PH was 1.06 (95% confidence interval 1.01–1. 12). There was no association between the probability of winning or placing on the sand track and PH. Conclusions and clinical relevance Direct measures of hoof conformation (HG and ML) were not related to racehorse performance in Macau. Lower PH was associated with better performance on a turf track. Further investigation into factors affecting PH and why it is related to performance are warranted. This study demonstrated that PH was associated with performance on a turf track. This information may be useful in the management and selection of Thoroughbred racehorses.